An evolutionary approach to the theory of entrepreneurship - Thomas Grebel; Andreas Pyka; Horst Hanusch (Universität Augsburg, Institut für Volkswirtschaftslehre, 2001)
The building blocks of our model are bounded-rational actors with specific sets of endowments: 'entrepreneurial spirit', human capital and venture capital. The entrepreneurial behavior to found a firm is triggered by the individuals' endowments, their social network and the evaluation of the economic situation. Bandwagon effects occur when high growth rates in emerging markets increase firm entries and firm entries in return increase growth rates until competition unfolds its selective power. The firms' survivability is determined by its founders endowments and its competitiveness. If actors are right or wrong in evaluating their economic situation and their consequent decisions is proven ex post. Thus, there will be winners and losers.
urn:nbn:de:bvb:384-opus4-712576
Keywords: O3; M13; 330; Entrepreneurship; human capital; venture capital; social networks; evolutionary economics; swarms of innovations